The The School Literacy Program: The Parental Role in Improving Literacy Skills on Online Learning of Elementary Students - Agustri, Diana; Suroyo, Suroyo; Yuliana, Ernik (International Journal of Elementary Education, 2023)
Parents who have a high level of education tend to understand more and think that education is very important for their children, so they prioritize education for their children. In addition, the way to educate children tends to be different between parents who have a high level of education and those with low education. The aim of this study is to analyze the parental role to improve literacy skills on students. This study is qualitative research with the subject is parents of students, moreover the Interview will be the instrument and data collection of this study. However, data collection of this using interview with survey method to get data from participants. However, data triangulation is data analyzing method for this study. The instrument used is a questionnaire. The population is 134 people, using a tolerance level of 5%, it can be seen that the number of samples in this study were 100 parents. The result found that Online learning is inseparable from problems that are obstacles in its literacy skills of elementary students, including online learning for elementary school students such as limited telecommunication networks. It is important to know the barriers for parents to assist their children to improve their literacy skills in online learning, solutions and projections of online learning for elementary school students.in conclusion, role of parents could take responsibility of their children in improving literacy skills through online learning for elementary school.